THE IMPACT OF URBAN GROWTH ON REGIONAL DEVELOPMENT OF AKURE METROPOLIS, ONDO STATE, NIGERIA - Adejompo FAGBOHUNKA (Analele Universităţii din Oradea: Seria Geografie, 2018)
The paper posits that the impact of urban growth could be understood from regional development perspective, using Akure metropolis, Ondo State, Nigeria as a case study. The first stage in the collection of primary data involves the reconnaissance survey of the study area, followed by the random administration of 25 questionnaires in each of the six identified quarters. Secondary data were also adopted, while data were descriptively and inferentially analyzed. The research revealed that one of the major causes of urban growth is employment opportunities, while the impact of urban growth on employment has not been satisfactory. The paper has found out that the impact of urban growth on economic activities was very good, whereas it was insignificant on infrastructural development. The research shows a fair impact of urban growth on health status, the paper also shows a positive relationship between urban growth and social vices. It was further revealed that the impact of urban growth on the standard of living and on the urban sprawl was fair and fairly significant respectively. The impact of urban growth on housing was not satisfactory. The paper shows that birth control measures could be adopted in mitigating the regional adverse effect of urban growth. It was further recommended that, in order to ensure urban tranquility, livability, socio-economic advancement and sustenance, government should create more employment, prioritizing increase in government expenditure and adequate security provision should be endeavoured.